Assessing the Correlation Between Creative Thinking and Mathematics Learning Success: A Meta-Analytical Perspective - Samritin; Rizkayati, Anisa; Safitri, Indah; Muqaddimah, Cahaya (Indonesian Journal of Educational Research and Review, 2024)
Creative thinking is a critical skill for students to develop in mathematics learning. Educational researchers have found an inconsistent relationship between creative thinking and success in mathematics learning. This meta-analysis aims to determine the overall relationship between creative thinking and mathematics learning success. The study employed a quantitative approach, utilizing data from primary studies published in academic journals. The sample was collected using the Publish or Perish application, resulting in 14 articles that met the inclusion criteria. The data were analyzed using correlation meta-analysis with the assistance of the JASP application. The analysis revealed that the correlation between creative thinking and mathematics learning success falls into the strong category. Additionally, the effect size of the correlation differed significantly across educational levels and between small and large sample sizes. However, no significant differences were observed in the effect size of the correlation based on the year of publication. These findings highlight the importance of fostering creative thinking skills in the mathematics learning process to enhance students' academic success.